Estudio de las propiedades de cementos óseos preparados con metacrilatos funcionalizados e hidroxiapatita - Vargas Coronado, R.; Cervantes Uc, J. M.; Cauich Rodríguez, J. V.; Vera Graciano, R.; Martínez Richa, A. (Revista Mexicana de Ingenieria Biomedica, 2001)
In this work, we report the synthesis of bone cement by using methyl methacrylate (MMA) as a base monomer and either methacrylic acid (MAA) or diethyl amino ethyl methacrylate (DEAEMA) as comonomers. Bioactive bone cement was obtained after hydroxyapatite (HA) addition in various concentrations. Then, a physicochemical characterization, with an emphasis on their mechanical behavior was conducted. Residual monomer content was found to vary with the composition of the matrix and ceramic concentration but never exceeded 4%. Curing times (tc), maximum temperatures (Tmax) and glass transition temperatures (Tg) depended on the presence of either MAA or DEAEMA. Bone cement prepared with MAA comonomer exhibited short curing times, high Tmax and Tg. On the other hand, DEAEMA containing bone cement showed long curing times, low Tmax and Tg. The addition of hydroxyapatite to these bone cement did not affect their maximum temperatures but increased curing times when DEAEMA was used as a comonomer or when MMA was used alone. All bone cement studied fulfilled the minimum compressive strength (70 MPa) required for bone cement use. However, the minimum tensile strength (30 MPa) was only fulfilled by cement prepared without filler and those composites containing either MMA or MAA. The minimum bending strength requirement (50 MPa) was not satisfied by any of the formulations studied.